Dinamika Pasar Monopoli dalam Ekonomi Mikro Syariah: Pengendalian Harga dengan Prinsip Keadilan - Yuda Admaja; Nisa Syahira Najla; Bagas Permana; Reni Ria Armayani Hasibuan (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2025)
This research explores how monopoly markets operate in the context of a sharia-based microeconomy, with a primary focus on how prices are regulated based on the principle of adl or justice. Unlike traditional monopolies, which often create inefficiencies in resource allocation and exploit consumers, Islamic teachings require fair prices, in accordance with the Quran's prohibition of gharar (uncertainty) and zulm (oppression). Referring to the theories of Ibn Taymiyyah and modern thinkers such as Chapra, we examine how monopoly companies can achieve maslahah or mutual benefit through profit restrictions, combining prices with zakat, and supervision by a sharia council. Through a simple mathematical model, we prove that monopolies regulated by justice produce better Pareto outcomes than equilibria that only maximize profits, by reducing social losses while still encouraging innovation. Empirical data from Islamic markets in Indonesia, such as halal commodities, support these findings, where regulations can stabilize prices at 15-20% lower. The conclusion of this study highlights the importance of Sharia principles in managing sustainable markets in developing countries, with policy recommendations to reform antitrust rules to align with the maqasid al-Shariah.